2017
DOI: 10.14202/vetworld.2017.187-193
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of mucosal nanoparticles and polymer-based inactivated vaccine for Newcastle disease and H9N2 AI viruses

Abstract: Aim:To develop a mucosal inactivated vaccines for Newcastle disease (ND) and H9N2 viruses to protect against these viruses at sites of infections through mucosal immunity.Materials and Methods:In this study, we prepared two new formulations for mucosal bivalent inactivated vaccine formulations for Newcastle and Avian Influenza (H9N2) based on the use of nanoparticles and polymer adjuvants. The prepared vaccines were delivered via intranasal and spray routes of administration in specific pathogen-free chickens.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 52 publications
3
9
0
Order By: Relevance
“…Numerous studies examined the immunoenhancing effects of Montanide oil IMS 1313 VG nanoparticle adjuvant vaccine formulations, and demonstrated encouraging efficacy against many pressing infectious threats (Sonia 2003;Jang et al, 2011 andNaggar et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies examined the immunoenhancing effects of Montanide oil IMS 1313 VG nanoparticle adjuvant vaccine formulations, and demonstrated encouraging efficacy against many pressing infectious threats (Sonia 2003;Jang et al, 2011 andNaggar et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…El Naggar et al (2017) designed preparation of mucosal NPs and polymer-based inactivated vaccine for Newcastle disease and H9N2 AI viruses, which after being delivered via intranasal and spray routes of administration in chickens enhanced the cell-mediated immune response and induced protection against challenge with both abovementioned viruses.…”
Section: Newcastle Disease Virusmentioning
confidence: 99%
“…Many researches have indicated that polymeric nanoparticles (NPs) can be used as potent adjuvants as Also these polymers have the ability to activate cellular immune response in the host by interact and activate various toll like receptors, thus involving several innate immune system players in immune response,this increase as a result of enhancing in IL6 and IFN  (El Naggar et al, 2017). The delivery of antigens to B cells via NPs has a co-stimulatory effect on Th cells, which helps to trigger specific antibody responses.…”
Section: Antibody Of Ibdmentioning
confidence: 99%
“…Interferons (IFNs) are important members of host innate arm of immunity to prevent virus infection by their antiviral effect (El-Naggar et al, 2017). IFN- produced by CD4+ T helper cell type 1 (Th1) lymphocytes, CD8+ cytotoxic lymphocytes and NK cells (Schroder et al, 2004).…”
Section: Interferon Gamma (Inf-) Levelmentioning
confidence: 99%